Transorbital Stab Injury with Retained Knife: A Narrow Escape - Muhammad Asim Rana; Abdulrehman Alharthy; Waleed Tharwat Aletreby; Basim Huwait; Akhilesh Kulshrestha (Case Reports in Critical Care)
Transorbital penetrating injuries are unusual but may cause severe brain damage if cranium is entered. These kinds of injuries are dangerous as the walls of orbit are very thin, hence easily broken by the otherwise innocent objects. Because of the very critical anatomical area involved, these injuries pose a serious challenge to the physicians who first receive them as well as the treating team. These may present as trivial trauma or may be occult and are often associated with serious complications and delayed sequel. Prompt evaluation by utilizing best diagnostic modality available and timely interference to remove them are the key aspects to avoid damage to vital organs surrounding the injury and to minimize the late complications. We report a case of transorbital assault with a 13 centimeter long knife which got broken from the handle and the blade was retained. The interesting aspect is that there was no neurological deficit on presentation or after removal.